Risk assessment and monitoring of Historic buildings. Comunicación en congreso. IV International Congress Science and Technology for the Conservation of cultural Heritage - Muñoz-González, Carmen María; León Rodríguez, D.; Navarro Casas, J.; Teeling, Catherine; Joyanes Díaz, María Dolores (My University, 2019)
One of the objectives of this work is hygrothermal behavior, in real time, of one set of historic buildings. The indoor and outdoor environment conditions have been parameterized and evaluated, and checked if current conditions are suitable for the preservation of artworks and buildings. This paper describes the methodology employed for the monitoring and presents the main results obtained. By other hand, as the cultural assets of these ecclesial heritages are located in worship spaces governed by institutions that, in general, haven’t got a museum structure, their con-servation taking account the new environmental techniques is questionable. Simulation models genereted reproduced the interior and exterior of the historic buildings, as well as constructive conditions and materials, in order to predict the environmental behavior of different processes of refusbisment.
Keywords: Edificios - Eficiencia energética; Heritage; Energy efficiency